Breast cancer management delay - time for improvement: A reflection from the eastern province of Saudi Arabia - Maha S.A Abdelhadi (Wolters Kluwer Medknow Publications, 2008)
Objective: Breast cancer is the commonest international malignancy among women. Its increased prevalence over recent years in our part of the world has prompted women to randomly seek medical advice. Many patients are delayed for weeks to months prior to receiving medical treatment. This review explores the causes of delay and proposes possible solutions. Materials and Methods: This review was undertaken at King Fahd Hospital of the University, a tertiary care center with the capacity of 420 beds. It accommodates a large number of referrals from the Eastern Province, other regions of the Kingdom, in addition to many walk-in patients. Most of the patients referred with breast cancer are directed to the breast clinic for treatment. There was random re-tracing of patients' steps from the discovery of the suspicious breast mass to the delivery of care. Results: The total number of diagnosed breast cancer cases at this center between 1997-2007 was 303, with a total number of 975 registered visits. Random retracing of these patients' records identified three points of delay: community related, primary heath care and tertiary care. It was found that the patients spent 6-15 weeks and around 32-38 hand offs before receiving the final care. Conclusion: This unnecessary delay creates anxiety and mistrust of the operating health system leading patients to seek alternative medicine or treatment abroad. A multidisciplinary one-stop breast oncology clinic may be the solution to the above problem. It may allow the fast tracking of breast cancer patients through a highly specialized and well-trained multidisciplinary team that offers the highest quality of care, thereby optimizing the chances of cure with the least delay and possible morbidity.